2008
DOI: 10.1093/dnares/dsn013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Genome Sequence of Porphyromonas gingivalis Strain ATCC 33277 and Genomic Comparison with Strain W83 Revealed Extensive Genome Rearrangements in P. gingivalis

Abstract: The gram-negative anaerobic bacterium Porphyromonas gingivalis is a major causative agent of chronic periodontitis. Porphyromonas gingivalis strains have been classified into virulent and less-virulent strains by mouse subcutaneous soft tissue abscess model analysis. Here, we present the whole genome sequence of P. gingivalis ATCC 33277, which is classified as a less-virulent strain. We identified 2090 protein-coding sequences (CDSs), 4 RNA operons, and 53 tRNA genes in the ATCC 33277 genome. By genomic compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
280
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(298 citation statements)
references
References 47 publications
13
280
0
5
Order By: Relevance
“…By protein BLAST (Basic Local Alignment Search Tool, https://blast.ncbi.nlm.nih.gov/) PGN_1185 has 98–100% amino acid identity to a GNAT acetyltransferase in 13 P. gingivalis strains with genome sequences deposited in GenBank [32]. According to HOMD (Human Oral Microbiome Database, http://www.homd.org/), there are 10 acetyltransferases in the ATCC 33277 genome [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By protein BLAST (Basic Local Alignment Search Tool, https://blast.ncbi.nlm.nih.gov/) PGN_1185 has 98–100% amino acid identity to a GNAT acetyltransferase in 13 P. gingivalis strains with genome sequences deposited in GenBank [32]. According to HOMD (Human Oral Microbiome Database, http://www.homd.org/), there are 10 acetyltransferases in the ATCC 33277 genome [32].…”
Section: Discussionmentioning
confidence: 99%
“…By protein BLAST (Basic Local Alignment Search Tool, https://blast.ncbi.nlm.nih.gov/) PGN_1185 has 98–100% amino acid identity to a GNAT acetyltransferase in 13 P. gingivalis strains with genome sequences deposited in GenBank [32]. According to HOMD (Human Oral Microbiome Database, http://www.homd.org/), there are 10 acetyltransferases in the ATCC 33277 genome [32]. Of these, six were annotated as follows: a probable serine acetyltransferase (PGN_0230); a metal binding acetyltransferase (PGN_0913); an alginate O-acetyltransferase (PGN_0943); a lipid phospholipid acetyltransferase (PGN_1142); a probable 1-acyl-sn-glycerol 3-phosphate acetyltransferase (PGN_1384); and a lysophospholipid acetyltransferase (PGN_2086).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutant in the PGN_0752 HK ( haeS ) from ATCC 33277 could not be generated using DNA primers designed from the W83 genome sequence, and in a previous study it was noted that the genomic region surrounding this TCS was highly divergent between the strains [52]. Following publication of the genome sequence of ATCC 33277 [53], a comparison of these regions revealed a 2.529 kbp deletion in ATCC 33277 at the locus homologous to haeSR (PG0719-720) in W83. Thus, ATCC 33277 is a naturally occurring mutant in the TCS.…”
Section: Haesr Systemmentioning
confidence: 99%
“…It was concluded that P. gingivalis uses domain rearrangements and genetic exchange to generate diversity in specific surface virulence factors. When the whole-genome sequences between ATCC 33277 and W83 were determined, extensive rearrangements were found between the two strains, possibly induced by different mobile elements (insertion sequences, miniature inverted-repeat transposable elements, and conjugative transposons) [10]. In ATCC 33277, many of the genes showed higher similarity to the genes of other bacterial species such as Bacteroides fragilis than to genes in W83.…”
Section: Introductionmentioning
confidence: 99%